Involvement of the ERK MAPK Cascade in the Formation of Adhesions in the Abdominal Cavity - I. A. Shurygina; M. G. Shurygin; L. V. Rodionova; E. E. Chepurnykh; N. I. Ayushinova (Acta Biomedica Scientifica, 2021)
Background. ERK1 and ERK2 (extracellular signal-regulated kinase) are related protein serine / threonine kinases that are involved in the regulation of the cell cycle, cell migration and survival, differentiation, metabolism, and proliferation. Evaluation of this cascade is promising to determine the possibility of influencing  pathological conditions through the regulation of ERK1/2.Aim of the study. To assess the involvement of the ERK MAPK cascade in the development of adhesions in the abdominal cavity.Methods. The experiments were carried out on male Wistar rats. The adhesion process in the abdominal cavity was simulated (n = 40). The research time is from 2 hours to 30 days. Tissue samples from 5 intact animals were examined as a control. Histological sections were prepared and stained histochemically for ERK1. The expression of ERK1 and ERK2 was assessed by PCR.Results. Using the PCR method, the involvement of both the ERK1 and ERK2 cascades in the process was established, and, judging by the change in gene expression, the latter is more actively involved in the process. Histochemical study confirmed the role of ERK cascades in the management of repair in serous membrane injury. Histochemically revealed an increase in ERK1 expression with two peaks of activity – at 1 and 30 days.Conclusion. Our data establish multichannel control of the reparative process in the area of damage to the serous membrane with the involvement of both the p38 and ERK MAPK cascades, which is important to consider when developing methods of influencing the wound healing process in the abdominal cavity.